Local control and toxicity outcomes following consolidative radiation therapy in patients with high-risk neuroblastoma: a 20-year experience at a single center - Jeong Yun Jang; Jin-Hong Park; Yeon Joo Kim; Ho Joon Im; Kyung-Nam Koh; Hyery Kim; Sung Han Kang; Ha Un Kim; Seung Do Ahn (The Turkish Journal of Pediatrics)
Background. Intensive multimodal treatment can improve survival in patients with high-risk neuroblastoma, and consolidative radiation therapy has contributed to local control. We examined the clinical outcomes of patients who underwent consolidative radiation therapy at our institution.